Mild ovarian stimulation with letrozole plus fixed dose human menopausal gonadotropin prior to IVF/ICSI for infertile non-obese women with polycystic ovarian syndrome being pre-treated with metformin: a pilot study - Giuseppe D'Amato; Anna Maria Caringella; Antonio Stanziano; Clementina Cantatore; Simone Palini; Ettore Caroppo (BMC, 2018)
Abstract Background Letrozole is widely employed as ovulation induction agent in women with PCOS, but its use in mild stimulation (MS) protocols for IVF is limited. Aim of the present study was to evaluate the feasibility of a MS protocol with letrozole plus hMG in non-obese PCOS women undergoing IVF after a metformin pre-treatment. Methods We retrospectively evaluated the data of 125 non-obese PCOS undergoing MS with letrozole plus hMG, 150 IU as starting dose, (group 1, N = 80) compared to those undergoing a conventional IVF stimulation protocols (CS) (group 2, N = 45) prior to IVF. All patients had received metformin extended release 1200-2000 mg daily for three to six months before IVF. GnRH antagonist was administered in both groups when the leading follicles reached 14 mm. Results Both groups were comparable for age, BMI and ovarian reserve markers. Both groups showed lower than expected AFC and AMH values as a consequence of metformin pre-treatment. Letrozole-treated patients required a significantly lower amount of gonadotropins units (p < 0.0001), and showed significantly lower day 5, day 8 and hCG day E2 levels compared to patients undergoing the CS protocol (p < 0.0001, p < 0.0001 and p = 0.001 respectively). The oocyte yield, in terms of total (6, IQR 3, vs 6, IQR 4 respectively,) and MII oocytes (5, IQR 3, vs 5, IQR 3, respectively) number, did not differ among groups; the number of total (3, IQR 2, vs 3, IQR 1 respectively) and good quality embryos (2, IQR1 vs 2, IQR 1,5 respectively) obtained was comparable as well in the two groups. The number of fresh transfers was significantly higher in group 1 compared to group 2 (80% vs 60%, p = 0.016). A trend for higher cumulative clinical pregnancy rate was found in women undergoing MS compared to CS (42.5%vs 24,4%, p = 0.044), but the study was not powered to detect this difference. Conclusions The present study suggests that the use of letrozole as adjuvant treatment to MS protocols for IVF may be an effective alternative to CS protocols for non-obese PCOS patients pre-treated with metformin, as it provides comparable IVF outcome without requiring high FSH dose, and avoiding supraphysiological estradiol levels.